Corrosion Behaviour of a Low Carbon Steel Piping Exposed to Different Water Conditions - Mahzan, Shahruddin; Rusli, Rus Izzati (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Although low carbon steel piping is broadly used due to its strength and wide availability, extensive exposure to water significantly affects its susceptibility to corrode. The main objective of this research is to investigate the corrosion behaviour of low carbon steel piping when exposed to different water conditions, which are seawater, lake water, and tap water. An immersion corrosion test was performed on low carbon steel piping samples to obtain corrosion rate based on the samples’ weight loss. Lake water produced the greatest weight loss at 0.24366 g, and the fastest corrosion rate, which is 0.4069 mmpy at the end of the test. The results show that this is due to the lake water’s qualities, especially the high level of dissolved oxygen (DO) of 8.59 ppm and its pH of 6.13 being the most acidic out of all the samples. Hence, these two parameters are significant in determining the rate of corrosion for low carbon steel piping exposed to water,